Consumer and Provider Perspectives on Technologies Used Within Aged Care: An Australian Qualitative Needs Assessment Survey. (December 2022) - Moyle, Wendy; Pu, Lihui; Murfield, Jenny; Sung, Billy; Sriram, Deepa; Liddle, Jacki; Estai, Mohamed; Lion, Katarzyna; ,
We undertook a qualitative assessment of aged care technology needs from the perspective of consumers and providers using a cross-sectional survey that assumed a largely open-response format. We recruited a convenience sample of individuals aged 18 years or older, lived in Australia, and self-identified as either an older adult ( n = 133), an informal caregiver of an older adult ( n = 27), and/or clinician, healthcare practitioner, and aged care provider ( n = 148). Survey responses were analyzed using a descriptive qualitative content analysis approach to interpret meaning from written survey responses. We identified seven themes reporting that technologies used in aged care do not appear to be meeting end-user needs. Supporting the Technology Acceptance Model, consumers and providers perceive usefulness of the technology and its actual ease of use as drivers of acceptance toward gerontechnology. Ten recommendations are proposed to support technology use and the quality of aged care.